2013
DOI: 10.1021/jp401310g
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally Mediated Photodissociation of CH3I [v1 = 1] at 277.5 nm: The Vibrationally Adiabatic Process

Abstract: From the photofragment translational spectra of C-H symmetric stretch excited CH3I [v1 = 1, v2 = 0] photodissociatioin at 277.5 nm, the vibrational distribution of photofragments CH3 (v1 = 0, v2 = 0), (0,1), (1,0), (1,1) in the I* channel are measured to be 0.02, 0.02, 0.47, 0.25, and those of CH3 (1,0), (1,1) in the I channel are 0.04, 0.05, respectively. It shows that most of the dissociated CH3I [1,0] retain the C-H symmetric stretch vibration v1 = 1 in the photofragments CH3, and the vibrational distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The fraction of excited molecules was probed by a scheme adapted from Hu et al ( 39 ). At first, the infrared excitation pulse was passed through the molecular beam entrained with CH 3 I.…”
Section: Methodsmentioning
confidence: 99%
“…The fraction of excited molecules was probed by a scheme adapted from Hu et al ( 39 ). At first, the infrared excitation pulse was passed through the molecular beam entrained with CH 3 I.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the initial vibrational excitation in the parent CH 3 I molecule was studied by the same authors 35 in a vibrationally mediated photodissociation experiment at 277.5 nm, where the CH 3 vibrational distribution produced in the photodissociation of CH 3 I(ν=0) and CH 3 I(ν 1 =1) molecules were compared. In addition, the TOF spectra measured at different pump and probe laser polarization configurations showed that the CH 3 fragments pro- duced in correlation with ground state I atoms are generated significantly hotter than those produced in the CH 3 (ν)+I * channel.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%
“…34,35 The CH 3 (ν 2 ) activity in the CH 3 +I channel has been traditionally assigned to the change in the equilibrium geometry of the umbrella bending angle occurring in the 1 Q 1 ← 3 Q 0 curve crossing. In the center of the Aband, the absorption is produced mainly to the 3 Q 0 state, which due to the similar CH 3 I equilibrium geometry with the ground state, preserves adiabatically the vibrational content of the parent molecule.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations